Economics of tea growing in Himachal Pradesh - Kumar, Virender; Jamwal, Neha; Sharma, Divya (The Indian Journal of Agricultural Sciences, 2020)
The present study was conducted in Palampur, Kangra district of Himachal Pradesh to examine the comparative economics of tea production on small and large tea farms (estates). The study was carried out during 2016 based on a random sample of 50 small tea growers and 3 tea estates chosen using stratified random sampling technique. The results of the study revealed that among different components of operational cost, the share of expenditure on human labour was highest (84-85%) on small farms as well as in estates. Per hectare tea leaf production was 54.5q in case of small and 57q on large tea farms. The cost of production on the small farms was observed to be `₹ 1, 561 per quintal while it was ₹ 1,356 in estates. The economic viability of tea production was higher in estates as compared to small farms partially due to mechanization of some operations and the economies of scale. Output-input analysis showed that the production of made tea was more profitable on estates as compared to small farms. Among the factors affecting tea production, labour days used, area under tea and experience in tea cultivation had positive and significant influence on production of tea. In order to boost tea production in the state, incentivized machine use in tea cultivation and enhancing marketing scope of homemade tea are some of the efforts that need attention of policy makers.